Policy Note : Environmental Management for a Sustainable Economic Development Strategy for Nanggroe Aceh Darussalam - World Bank (Washington, DC, 2013)
This policy note, Environmental Management for a Sustainable Economic Development Strategy for Nanggroe Aceh Darussalam, investigates six environmental management topics which will affect the capacity of the province to develop the economy and need to be underpinned by strong environmental and natural resource management. The six topics cover: agriculture, forestry, fisheries, land and water, environmental law and regulations, and spatial planning. Each topic provides the context for and some background on the sector, key issues facing the management of the sector, potential sustainable development opportunities and initiatives and recommendations on actions to improve the development and management of the sector. The policy note includes a framework to develop nine elements of an enabling environment that would support the development of the province's natural resources, as well as a set of specific recommendations and initiatives.